Analysis of Medical Records Management Systems in Improving the Quality of Health Services: Systematic Literature Review - Devi Delvita; Afrileo Vebi Eka Utama (Universitas Ibn Khaldun Bogor, 2026)
A medical records management system is a crucial component in improving the quality of healthcare services because it serves as a source of clinical, administrative, and legal information, as well as for evaluating service quality. Good implementation of medical records, particularly Electronic Medical Records (EMR), can improve service effectiveness, accelerate access to patient information, enhance documentation accuracy, and support patient safety. The purpose of this study was to examine the analysis of Medical Records Management Systems in Improving Healthcare Service Quality. The method used was a Systematic Literature Review (SLR) by examining quantitative journal articles from 2022–2025 that discussed medical records management and healthcare service quality. The results found that the implementation of Electronic Medical Records (EMR) has a positive impact on service effectiveness, time efficiency, patient data security, and medical documentation accuracy. It can be concluded that EMR has a positive impact on healthcare service quality, particularly in aspects of speed of patient data access, information security, continuity of service, and reduction of medical recording errors. Furthermore, an integrated medical records system also contributes to increased patient satisfaction and healthcare worker performance by making the service process more structured and effective.